Pengembangan Embedded Device Berbasis PLC untuk Simulator Rejection System dengan Penambahan Human Machine Interface - Riyandar Riyandar; Muhamad Wildan; Arief Goeritno; Joki Irawan (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
Changes to the simulator rejection system from the previous research were carried out by replacing all sensors, drive motors, PLC systems, and adding HMI systems. The objectives in this research, namely (i) changing and developing a rejection system simulator, creating a ladder-based program structure and configuring HMI systems and (ii) measuring the performance of the simulators. Rejection system simulator is fabricated and reassembled, ladder-based syntax into PLCs and HMI is also configured, and observing the performance is done through the HMI layer. The results of programming is carried out through (i) providing software for PLCs, (ii) programming the PLC system, (iii) compiling and uploading programs from PC to PLC, (iv) configuring PLC and HMI via ethernet, and (v) compiling and uploading the program structure from PC to HMI. The performance for observing the condition of the bottle cap through the HMI is observed when (i) synchronization between the simulator system and the HMI-assisted PLC control, (ii) the reading of the sensors installed on the simulator, and (iii) the rotation process of the rejector arm. Overall, the rejection system simulator with a PLC-based assisted by HMI can be used as a process simulation against the implementation of the rejection system